For a ‘re-cognition’ of the Law - Robertazzi, Mariella (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The frequent crises of the criminal system led to an increase in the use of extra-judicial, informal methods of response to the crime. One of the main examples is restorative justice, whose programs refer to some key concepts such as: listening, dialogue, empathy, trust, recognition. However, these aspects are present first and foremost in what could be defined as a whole notion of law, that is not reduced to its authoritative and coercive dimension. Using the category of recognition, the paper reaffirms how the human relational nature constitutes the necessary premise for the existence of the law. In this regard, the current debate on restorative justice is an additional opportunity to critically re-discuss a somehow exclusive and reductive vision of the law.